Use of amitriptyline, bupropion and agomelatine in the treatment of non-depressive disorders: a review of mechanisms and therapeutic indications - Piotr Czerniak; Julia Buszek; Michał Medygrał; Przemysław Koszuta; Małgorzata Dydoń-Pikor; Katarzyna Pajdak-Gicala; Maciej Kawecki; Adrianna Antoszewska; Weronika Bargiel; Sylwia Buszek (Quality in Sport)
Introduction